Pengaruh Penerapan Green Accounting, Material Flow Cost Accounting, dan Environmental Performance terhadap Profitabilitas Perusahaan - Oktadifa, Rani Melati; Widajantie, Tituk Diah (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research was conducted with the aim to determine how the influence of the application of green accounting, material flow cost accounting, and environmental performance by companies in increasing company profitability as measured using return on asset (ROA). This research was conducted using quantitative methods. The research sample is 18 companies in the primary consumption sector (consumer non-cyclicals) listed on the Indonesia Stock Exchange during the 2018 – 2021 period which were selected using a purposive sampling technique. The data in this study is secondary data in the form of the company's annual report, which is obtained through the official website of each company. Data analysis was carried out using SmartPLS 4.0 software The results show that green accounting and environmental performance have a significant positive effect on company profitability, which means that a high level of company concern for the environment will be able to increase company profits every year. Meanwhile, material flow cost accounting has no effect on company profitability because it is estimated that material flow cost accounting has included in environmental disclosures. Keywords: green accounting, material flow cost accounting, environtmental performance, return on asset